Cross-influence of Risk, Return, and Governance on Decision-Making in Hydropower Investments - Karki, Dipendra (Economic Journal of Development Issues, 2024)
The sustainable growth of an economy pivots on a robust financial system, particularly in the context of capital availability. This study analyzes the behavior of investors towards initial public offerings (IPOs), focusing on the hydropower development sector in Nepal. The research explores the multifaceted relationship between factors such as risk, return, and governance on investor behavior, considering elements like Idiosyncratic risk (IR), timing of issue (TIPO), Bandwagon effect (BE), expected return (ER), sectoral performance (SP), corporate governance (CG), pre-issue financial health (PFH), and marketability (MKT). Additionally, sociodemographic variables and their connection to investor behavior are examined. Employing a descriptive research design, the study involves a sample size of 392 individuals, selected through a convenient sampling method. The study’s main finding documented that idiosyncratic risks, expected returns, and corporate governance stand out as crucial factors influencing investment decisions (P < 0.05). Notably, the regression analysis indicated the absence of a significant impact from market risks (P > 0.05), including the bandwagon effect and IPO timing, on investor behavior towards hydropower IPOs. This finding suggests that Nepalese investors prioritize returns and organizational governance over market risks, despite having significant concerns regarding idiosyncratic risk. The analysis also reveals significant associations between investor behavior and sociodemographic variables like age, education, occupation, and primary investment objectives (P < 0.05). This study offers valuable insights and implications for investors seeking to align investments with their goals. Hydropower developers should prioritize investor protection and transparency, while regulators must enhance disclosures, shareholder accountability, and project oversight.